2021
DOI: 10.3390/brainsci11121603
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Analysis of Plasmalogens in the Hippocampus of an Alzheimer’s Disease Mouse Model: A Role of Ethanolamine Plasmalogen

Abstract: Plasmalogens are alkenyl-acyl glycerophospholipids and decreased in post-mortem Alzheimer’s disease (AD) brains. The aim of this study is to investigate the time-dependent changes of plasmalogens in the hippocampus of an AD model mouse (J20). Plasmalogen levels at 3, 6, 9, 12 and 15 months were analyzed by liquid-chromatography-targeted-multiplexed-selected-reaction-monitoring-tandem-mass-spectrometry (LC-SRM/MS). Reactive oxygen species (ROS) levels were evaluated using dichlorofluorescein diacetate (DCF-DA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Second, most of these studies were conducted on the whole brain 32 , 35 with few having assessed specific brain areas (e.g. hippocampus 24 , 36 , cortex 34 , 37 ), it would therefore be interesting to consider other areas simultaneously. Third, the mice age ranged from 2 to 24 months 28 , 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Second, most of these studies were conducted on the whole brain 32 , 35 with few having assessed specific brain areas (e.g. hippocampus 24 , 36 , cortex 34 , 37 ), it would therefore be interesting to consider other areas simultaneously. Third, the mice age ranged from 2 to 24 months 28 , 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, plasmalogens can protect lipid bilayers against the damaging effects of oxidation by scavenger radicals, such as ROS and reactive nitrogen species. As such, decreased plasmalogen concentrations may increase one's susceptibility to developing neurodegenerative or neuroinflammatory disorders, such as Alzheimer's disease (Azad et al., 2021; Han et al., 2001), Parkison's disease, or MS (Ferreira et al., 2021; Mawatari et al., 2020). Here, we demonstrate that FTY720 increases plasmenyl‐PE levels from 17.0% to 20.5% of the total lipid composition of the mouse hippocampus, which may increase the resistance of vulnerable neurons to oxidative stress (Zoeller et al., 2002) and explain why other studies have found that FTY720 can reverse cognitive deficits in animal models of CNS diseases (Fagan et al., 2022; Udagawa & Hino, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with literature, consistently showing a decrease in plasmalogen levels in different brain regions or CSFs in AD patients [ 26 , 48 , 68 , 69 , 70 , 71 , 72 , 73 ]. Furthermore, reduced plasmalogen levels can be found in AD mouse models [ 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%